Automated DMS for laboratory monitoring / Mohd Fazly Mohd Redzuan - Mohd Redzuan, Mohd Fazly (2008)
This paper presents the development of software programming to manage data for laboratory monitoring application. This system use personal computer (PC) or laptop as a processor device in conjunction with analog and digital input or output from the oscilloscope and the signal source by using interface technology. The software use windows-based application and graphical user interface (GUI) support. The system will show the output signal wave form at the panel interface that was design for further analysis. The system also will show the result value of voltage and frequency from the output signal wave. The appropriate subsystem, Microsoft Visual Basic 6.0 is used as the programming language to perform the task associated with the analysis of the wave from the signal generator.